PENGEMBANGAN PROTOTIPE VOIP UNTUK TELEMETRI SISTEM PERINGATAN DINI BANJIR - , Munawal Ulfiyanto ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Flood Early Warning System is a system designed to detect flooding and provide a warning to prevent casualties. In the flood early warning system has two stations are monitoring stations and warning stations that are not in one location, so it requires a telemetry. It will be conducted a research to use VoIP (Voice over Internet Protocol) which function to call as well as telemetry. Many aspects underlying the use of VoIP for telemetry flood warning system are as follows : a. Using SIP (Session Initiation Protocol), which can represent or have the necessary communication systems in flood early warning system. b. Based on IP (Internet Protocol), which can use the local district Intranet, thus reducing the cost of preface to a new communications equipment. c. Controlled local districts without special treatment, but done with self-help system. d. Sensor can be integrated with rainfall and water level, so it can automatically send a warning. With this research are expected to be a reference for the areas you want menerepkan flood early warning system. And after the research is expected the development of a protocol for telemetry flood warning system. The research was done by observation through a case study on flood early warning system Sragen Regency, continued design and manufacture of prototype VoIP for telemetry flood warning.